Pengaruh Endorphin Massage Terhadap Kecemasan Ibu Hamil Trimester III Gravida 1 di Puskesmas Maracang Tahun 2024 - Friska, Deka; Masliyah, Elly (CV. Green Publisher Indonesia, 2025)
Anxiety in pregnant women, especially the third trimester on Gravida 1, can affect the quality of labor. Endorphin massage is one of the non-pharmacological therapies that aims to stimulate the release of endorphins to provide a relaxing effect and reduce anxiety. This study aims to determine the effect of endorphin massage on anxiety of pregnant women in the third trimester at the Maracang Health Center. The study used Quasi-Experimental with a Pretest-Posttest Control Group Design, involving 30 respondents. Anxiety levels were measured before and after the intervention using the Zung Self-rating Anxiety Scale (ZSAS). Before the intervention, the majority of respondents experienced moderate anxiety (60.0%). After the endorphin massage intervention, there was a significant decrease in anxiety levels, with the majority of respondents experiencing mild anxiety (63.4%). Statistical tests showed a p-value of 0.000, indicating that endorphin massage has a significant influence on reducing anxiety in pregnant women in the third trimester. Endorphin massage is effective in reducing anxiety for pregnant women in the third trimester Gravida 1 at the Maracang Health Center in 2024. Midwives are advised to use endorphin massage as a non-pharmacological intervention to reduce anxiety in pregnant women, as well as provide education related to anxiety management during pregnancy to pregnant women and their families.